Catalytic valorization of glycerol to hydrogen and syngas - Lin, Yu-Chuan (International journal of hydrogen energy, 2013)
Glycerol, a byproduct derived from the production of biodiesel, is currently in an oversupply crisis worldwide. One approach to alleviate this problem is to transform glycerol into valuable chemicals such as hydrogen and syngas. Pyrolysis, steam reforming, partial oxidation, autothermal reforming, and aqueous-phase reforming are promising routes for the catalytic conversion of glycerol. However, certain challenges are still limiting their development. Recent advances in catalyst design, reactor engineering, and theoretical chemistry have enabled us to understand glycerol valorization on macro- and microscopic scales, and may help overcome existing thresholds. With the synergistic efforts of these tools, glycerol may no longer be a burden, but a valuable resource of hydrogen and syngas in the near future. ► A review of glycerol conversion to hydrogen and syngas. ► Pyrolysis, steam reforming, partial oxidation, and aqueous-phase reforming. ► Computational studies provide in-depth understandings of glycerol valorization.